The art of designing embedded systems - Ganssle, Jack G. (Boston, Mass. : Newnes, 2000)
Art of Designing Embedded Systems is apart primer and part reference, aimed at practicing embedded engineers, whether working on the code or the hardware design. Embedded systems suffer from a chaotic, ad hoc development process. This books lays out a very simple seven-step plan to get firmware development under control. There are no formal methodologies to master; the ideas are immediately useful. Most designers are unaware that code complexity grows faster than code size. This book shows a number of ways to linearize the complexity/size curve and get products out faster. Ganssle shows ways to get better code and hardware designs by integrating hardware and software design. He also covers troubleshooting, real time and performance issues, relations with bosses and coworkers, and tips for building an environment for creative work. Get better systems out faster, using the practical ideas discussed in Art of Designing Embedded Systems. Whether you're working with hardware or software, this book offers a unique philosophy of development guaranteed to keep you interested and learning. * Practical advice from a well-respected author * Common-sense approach to better, faster design * Integrated hardware/software.
Disciplined development -- Stop writing big programs -- Real time means right now! -- Firmware musings -- Hardware musings -- Troubleshooting tools -- Troubleshooting -- People musings.
Includes index.
Keywords: Embedded computer systems -- Design and construction; Embedded computer systems -- Design; Electronic books